Pengaruh Perbandingan Fase Minyak Virgin Coconout Oil (Cocos nucifera L.) dan Lemak Kakao (Theobrama Cacao L.) serta Suhu terhadap Karakteristik Sediaan Krim - Prasatya, I Kadek Aditya; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): JuniDO - 10.24843/JRMA.2020.v08.i02.p07, 2020)
Virgin coconut oil turn into liquid based in a room temperature  that has lot of vitamin E and coconut acid. Cocoa butter is solid in temperature that has lot of stearic acid. This research aims to know the temperature effects and comparation of oil phase , virgin coconut oil : cocoa butter in the characteristic of  cream based determine the temperature and comparation of oil phase (virgin coconut oil : cocoa butter) to produce cream based. The trial design in this research was the second factorial trial. This reasearch used factorial randomized  block. First factorial was the comparation oil phase of virgin coconut oil : cocoa butter consist of 3 levels, that is 1:3, 1:5 a nd 1:7. While in the second factorial the was heating temperatures, consist of 3 levels that is 60±2°C, 70±2°C and 80±2°C. The comparation treatments of oil phase virgin coconut oil : cocoa butter that really affected the viscosity, cohenren power, diameter of spread power and seperation ratio, heating temperature really affected with diameter of spread power and coherent power. Tempererature treatment and comporation of oil phase affected the diameter of spread power. The temperature treatment and oil phase ratio have a very significant effect on the dispersal power. Comparison of VCO and cocoa butter treatment (1:7) with a temperature of 80±2°C is the best treatment to produce cream preparations with characteristics of a homogeneous cream, viscosity (46 .000 cp), cohenren power (9 ,77 seconds), diameter of spread power (7 ,075 cm), separator ratio (0 ,27 cm) and pH (6 ,65). Keywords:  Virgin coconut oil,  cocoa butter, temperature, characteristic, based cream.